On geomagnetic storms and associated solar activity phenomena observed during 1996–2009. (April 2016) - Mittal, Nishant; Verma, V.K.
Abstract: Here we present study of Geomagnetic storms (GMS) and its relation with solar flares, coronal mass ejections (CMEs) and coronal holes (CHs). The arrival of CMEs in the vicinity of the Earth plays an important role and affects solar terrestrial environment. The space weather prediction about GMS can be only possible if we know the CMEs arrival time at 1 AU. In the present study we have investigated 153 CMEs observed during the time period of 1996–2009 to know the arrival times of CMEs associated with the GMS. In study we found that the strength of GMS didn׳t depend on the speed and accelerations of CMEs but strength of GMS depend on the importance of solar flares. We also found that the strength of GMS are excellently correlated with southward magnetic field near Earth at 1 AU and support earlier result of investigators. The arrival time of CMEs near Earth at 1 AU, can be calculated using equations for linear and initial speed of CMEs with error ±5 h. We have also discussed the various results obtained in present investigation in view recent scenario of solar helio-physics. Highlights: Strength of GMS didn׳t depend on the speed and accelerations of CMEs. Strength GMS depend on the importance of solar flares. Strength of GMS is correlated with southward magnetic field near Earth at 1 AU. We have tried to predict arrival time of CMEs in the vicinity of Earth at 1 AU.